California agricultural research priorities : Pierce's disease - National Research Council (U.S.). Committee on California Agricultural Research Priorities: Pierce's Disease (Washington, DC : National Academies Press, 2004)
"The glassy-winged sharpshooter is one of the more recent invasive pests to afflict California agriculture. The insect transmits a bacterial pathogen that causes Pierce's disease, which has impaired production of wine, table, and raisin grapes in California. The report recommends strengthening the process and the priorities for research funded by state agencies and wine industry groups to address Pierce's disease and its vector. Research should be focused on identifying feasible options for controlling the spread of the disease and providing sustainable approaches that are adaptable and affordable over the long term. Several avenues of research be pursued more intensely including the genetic makeup of the pathogen that triggers Pierce's disease, understanding the mechanisms that make grapes resistant to the disease, the possibilities of introducing predator enemies to the sharpshooter, and new ways to manage the planting of crops to help avoid spread of the disease."--
""FrontMatter""; ""Reviewers""; ""Preface""; ""Contents""; ""Tables, Figures, and Boxes""; ""Executive Summary""; ""1 Pierceâ€?s Disease and the Glassy-winged Sharpshooter: Their Biology and the Challenges of Their Management""; ""2 Developing Priorities for Research""; ""3 Hostâ€?Vector Interaction""; ""4 Plantâ€?Pathogen Interaction""; ""5 Vectorâ€?Pathogen Interaction""; ""References""; ""Appendix A Committee Biographies""; ""Board on Agriculture and Natural Resources Publications""
Includes bibliographical references (pages 114-151).
Print version record.
eBooks on EBSCOhost
Keywords: Pierce's disease -- California; Grapes -- Diseases and pests -- California; Leafhoppers -- Control; Insects as carriers of plant disease; Vigne -- Maladies et fléaux -- Californie; Cicadelles -- Lutte contre; Insectes (Vecteurs de maladies des plantes); TECHNOLOGY & ENGINEERING -- Agriculture -- General; GARDENING -- Fruit; Grapes -- Diseases and pests; Insects as carriers of plant disease; Leafhoppers -- Control; Pierce's disease; California; Computer network resources